2022
DOI: 10.1088/1748-9326/ac9e0a
|View full text |Cite
|
Sign up to set email alerts
|

Natural climate solutions in Indonesia: wetlands are the key to achieve Indonesia’s national climate commitment

Abstract: Indonesia offers a dramatic opportunity to contribute to tackling climate change by deploying Natural Climate Solutions (NCS), increasing carbon sequestration and storage through the protection, improved management, and restoration of drylands, peatlands, and mangrove ecosystems. Here, we estimate Indonesia's NCS mitigation opportunity for the first time using national datasets. We calculated the maximum NCS mitigation potential extent using datasets of annual national land cover, peat soil, and critical lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This figure is smaller compared to the results presented in Miettinen et al (2016), which found that 70.8–93.6% of the total peatland areas were degraded. Using a similar historical baseline, Novita et al (2022) reported that 8.7 Mha of degraded peatlands in Indonesia have the potential to be restored through rewetting and improved water table management in agricultural sites. Nevertheless, both studies have several key differences in the datasets and methods used to determine the potential restoration areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This figure is smaller compared to the results presented in Miettinen et al (2016), which found that 70.8–93.6% of the total peatland areas were degraded. Using a similar historical baseline, Novita et al (2022) reported that 8.7 Mha of degraded peatlands in Indonesia have the potential to be restored through rewetting and improved water table management in agricultural sites. Nevertheless, both studies have several key differences in the datasets and methods used to determine the potential restoration areas.…”
Section: Discussionmentioning
confidence: 99%
“…To date, Indonesia's peat restoration program has been relying on funding from the state, international donors, and private sectors, including non‐governmental organizations (Puspitaloka et al 2021). Even though peat restoration is listed as one of the main climate mitigation strategies to achieve Indonesia's Nationally Determined Contribution and Forestry and Other Land Use Net Sink Target (MoEF 2022), with a recent study estimating that it could help reduce GHG emissions up to 269 MtCO 2 /year (Novita et al 2022), the government still prioritizes climate mitigation budget on the transportation and energy sectors (MoEF 2020). It is estimated that peat restoration in Indonesia needs a projected cost of $1.7–7.0 billion USD (Kiely et al 2021; Sari et al 2021) with an average cost of $1,866 USD per hectare for restoration (Hansson & Dargusch 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About half of peatlands in this region are currently degraded and under serious threats due to extensive peatland drainage and land use change that have caused significant carbon emissions 11 14 . However, a recent study 15 concluded that tropical peatlands in Indonesia have the potential to contribute up to 74% of the total maximum national mitigation potential from natural climate solutions through both conservation and restoration efforts. Therefore, conserving and restoring tropical peatland ecosystems in Indonesia is pivotal for climate change mitigation and thus fulfilling national climate commitments.…”
Section: Introductionmentioning
confidence: 99%
“…Once intact mangroves are disturbed and converted to other land uses, they generate substantial greenhouse gas (GHG) emissions [7][8][9][10][11][12]. Indonesia lost approximately 30% of its mangrove forests between 1980 and 2005 [13], or an estimated GHG emissions of 0.19 Pg CO 2e yr − 1 [12]. A recent study showed that the mangrove deforestation rate in Indonesia from 2009 to 2019 was estimated at 18,209 ha yr − 1, resulting in total emissions of 1,434,874 Mg CO 2e ha − 1 yr − 1 , which comprised approximately 10% of the total projected emissions from the total forestry sector in Indonesia (2006-2020) [6].…”
Section: Introductionmentioning
confidence: 99%